A Database of Simultaneously Recorded ECG Signals With and Without EMG Noise - Vladimir Atanasoski; Jovana Petrovic; Lana Popovic Maneski; Marjan Miletic; Milos Babic; Aleksandra Nikolic; Dorin Panescu; Marija D. Ivanovic (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: Noise on recorded electrocardiographic (ECG) signals may affect their clinical interpretation. Electromyographic (EMG) noise spectrally coincides with the QRS complex, which makes its removal particularly challenging. The problem of evaluating the noise-removal techniques has commonly been approached by algorithm testing on the contaminated ECG signals constructed ad hoc as an additive mixture of a noise-free ECG signal and noise. Consequently, there is an absence of a unique/standard database for testing and comparing different denoising methods. We present a SimEMG database recorded by a novel acquisition method that allows for direct recording of the genuine EMG-noise-free and -contaminated ECG signals. The database is available as open source.